Building a Regional Halal Industry Ecosystem: The Roles of Halal Certification, Digital Economy, and Islamic Financial Institutions among MSMEs in Tanah Datar Regency - Elmiliyani Wahyuni; Husni Shabri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Background. The development of a sustainable halal industry ecosystem requires the integration of halal certification, digital transformation, and the support of Islamic financial institutions. However, at the regional level, the effectiveness of these components in strengthening the halal industry ecosystem remains empirically underexplored, particularly in areas with strong Islamic socio-cultural foundations such as Tanah Datar Regency. Purpose. This quantitative study aimed to examine the influence of halal product certification, the digital economy in the MSME sector, and the role of Islamic financial institutions on the halal industry ecosystem. Specifically, it investigated whether these three determinants significantly contribute to strengthening the halal ecosystem among halal-certified MSMEs in Tanah Datar. Method. The study involved 92 halal-certified MSMEs selected from a population of 953 business units using purposive sampling and Slovin’s formula. Primary data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Validity and reliability tests were conducted prior to hypothesis testing through bootstrapping procedures.. Results. The findings indicate that halal product certification has a positive and significant effect on the halal industry ecosystem. In contrast, the digital economy variable and the role of Islamic financial institutions do not show a statistically significant influence. The structural model explains 45.4% of the variance in the halal industry ecosystem, indicating a moderate predictive capacity. Conclusion. This study highlights that strengthening the halal ecosystem at the regional level is primarily driven by the legitimacy and assurance provided by halal certification. The findings imply that policy interventions should prioritize accelerating certification programs while simultaneously improving digital literacy and optimizing Islamic financial inclusion to enhance long-term ecosystem sustainability.